2004
DOI: 10.4319/lo.2004.49.5.1848
|View full text |Cite
|
Sign up to set email alerts
|

A species invasion mediated through habitat structure, intraguild predation, and parasitism

Abstract: With field, laboratory, and modeling approaches, we examined the interplay among habitat structure, intraguild predation (IGP), and parasitism in an ongoing species invasion. Native Gammarus duebeni celticus (Crustacea: Amphipoda) are often, but not always, replaced by the invader Gammarus pulex through differential IGP. The muscle-wasting microsporidian parasite Pleistophora mulleri infects the native but not the invader. We found a highly variable prevalence of P. mulleri in uninvaded rivers, with 0-91% of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Table 1). A minor importance of predation in the field compared to a higher importance in laboratory studies might be due to the more complex conditions and available food resources in the field, as the predatory strength of amphipods can be influenced not only by habitat structure but also by both abiotic and biotic conditions (Dick & Platvoet, 1996;MacNeil et al, 2004). Furthermore, the low inter-individual agreement in detected macroinvertebrate DNA in guts of individuals from the same site might be a hint that individuals are not feeding on the same resource pool.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1). A minor importance of predation in the field compared to a higher importance in laboratory studies might be due to the more complex conditions and available food resources in the field, as the predatory strength of amphipods can be influenced not only by habitat structure but also by both abiotic and biotic conditions (Dick & Platvoet, 1996;MacNeil et al, 2004). Furthermore, the low inter-individual agreement in detected macroinvertebrate DNA in guts of individuals from the same site might be a hint that individuals are not feeding on the same resource pool.…”
Section: Discussionmentioning
confidence: 99%
“…Wodarz & Sasaki (2004), in a model of competing species each harbouring a parasite lethal to its competitor, showed that the parasites could enforce species boundaries, creating zones where a competitor cannot invade because of encounter with the lethal parasite. MacNeil et al. (2004) show that the prevalence of microsporidian infection in the native G. d. celticus is heterogenous across habitat patches; models demonstrated a ‘bridgehead’ effect, whereby the invasive G. pulex could succeed by first replacing natives in infected patches; invasion would not succeed in a homogenous environment.…”
Section: Future Challengesmentioning
confidence: 99%
“…Thermal responses are understood to be an underlying mechanism behind predator -prey dynamics (Berlow et al 2009;Rall et al 2010;Englund et al 2011), but predicting the outcome of such interactions under future abiotic scenarios is highly problematic (Le Quesne and Pinnegar 2011). This is partly due to multiple layers of real world complexities such as habitat heterogeneity (MacNeil et al 2004;Ferner et al 2009;Alexander et al 2015;Barrios-O'Neill et al 2015), light (Koski and Johnson 2002), multiple predator effects (Lang et al 2012;Alexander et al 2013;Wasserman et al 2016a). The apparent species specificity of thermal dynamics poses an additional layer of difficulty in response prediction due to the metabolism of different species having varying sensitivity to temperature effects and therefore producing differential responses (Lang et al 2012).…”
Section: Introductionmentioning
confidence: 99%